A Meta-Analysis of Police Response Models for Handling People With Mental Illnesses: Cross-Country Evidence on the Effectiveness. (June 2021) - Seo, Chunghyeon; Kim, Bitna; Kruis, Nathan E.
Recent global statistics on mental health showed that the number of people with mental illnesses has dramatically increased in many countries. A gatekeeper to the criminal justice system, police have begun to develop their own police response programs or have adopted renowned models from other countries for handling people with mental illnesses. Although there is a growing body of empirical research that has investigated the effectiveness of police response models for handling the mentally ill (PRMHMI) in various countries, existing systematic reviews or meta-analytic studies have disproportionately focused on findings from studies testing the effects of the crisis intervention team in the United States. Thus, it is still not clear whether PRMHMI can be considered as "evidence-based" models on the international level. To help fill this gap in the literature, the current systematic review and meta-analysis compared the effectiveness of PRMHMI operating in the United States to those operating in other countries including the United Kingdom, Australia, Canada, and Liberia. Results revealed that the effect sizes of PRMHMI were substantially different across countries. This study's results demonstrate the importance of a national context for designing, implementing, and evaluating PRMHMI.